Clinical spectrum in CADASIL family with a new mutation - Peisker, Tomas; Musil, Libor; Hrebicek, Martin; Vlaskova, Hana; Cihelkova, Ilona; Bartos, Ales (Biomedical papers, 2013)
Background: Clinical presentation of CADASIL patients is variable due to the impact of other vascular risk factors and the type of a NOTCH3 mutation. This variability may impede the diagnosis of the disease.Subjects and Methods: We report a comprehensive evaluation of several individuals in the CADASIL family whose member was identified to have the new mutation of NOTCH3 receptor on exon 6 (p. G296C). We performed genetic testing, clinical and neuropsychological examination, cerebral MRI, Doppler sonography of cerebral arteries, fundoscopic examination and fluorescent angiography in six family members to determine the corresponding clinical spectrum associated with the new mutation.Results and Conclusion: The CADASIL mutation was detected in four individuals. Three of them were symptomatic, two having a history of stroke and one suffering from migraine. Although individuals had heterogeneous findings, the common feature included vascular changes that were present on cerebral and/or retinal arteries in all the mutation carriers even in one subject without clinical manifestation of the disease.
Keywords: CADASIL; NOTCH3; stroke; migraine; fluorescent angiography; Doppler